A capped trigonal prismatic cobalt(ii) complex as a structural archetype for single-ion magnets. Issue 7 (30th January 2020) - Yi, Gangji; Cui, Huihui; Zhang, Chunyang; Zhao, Wen; Chen, Lei; Zhang, Yi-Quan; Chen, Xue-Tai; Song, You; Yuan, Aihua
Abstract : Mononuclear, seven-coordinate complex [Co II (BPA-TPA)](BF4 )2 (BPA-TPA = pentapyidyldiamine) display field-induce slow magnetic relaxation, thereby presenting the first report of SIMs based on 3d metal ions with a capped trigonal prismatic geometry. Abstract : Two mononuclear, seven-coordinate Co(ii ) and Fe(ii ) complexes [Co II (BPA-TPA)](BF4 )2 (1-Co ) and [Fe II (BPA-TPA)](ClO4 )2 (2-Fe ) with a capped trigonal prismatic coordination geometry have been synthesized from the pentapyridyldiamine (BPA-TPA) ligand. 1-Co exhibits easy plane anisotropy in which slow magnetic relaxation is observed under a 1.0 kOe dc field. It is the first example of a single-ion magnet (SIM) of a 3d transition metal ion with a capped trigonal prismatic configuration. 2-Fe is not a SIM at 1.8 K.